Rice Husk Based Zeolite As Methane Adsorbent - Kamarudin, K. S. N.; Wah, L. M.; Yuan, C. Y.; Hamdan, H.; Mat, H. (2004)
Rice husk ash (RHA) is a good alternative source for the production of zeolite since it contains more than 95% silica. The content of silica and carbon in rice husk were varied depending on combustion temperature, thus varies the properties of zeolite produced. Unlike typical post synthesis modification where non-polar materials are introduced into zeolite structures, carbon is included into zeolite during the hydrogel formation as it is present in RHA. To study the potential use of RHA based zeolite on gas adsorption, RHAs obtained from different combustion temperatures (450 â€“ 800Â°C) will be used to synthesize zeolite under hydrothermal condition. The differences in structural properties and gas adsorption characteristics from different RHAs were analysed. It was found that RHA properties affect structural formation of zeolite, physicochemical properties as well as methane adsorption behavior.